2023
DOI: 10.1001/jama.2023.8867
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Lipid Disorders in Children and Adolescents

Abstract: ImportanceLipid screening in childhood and adolescence can lead to early dyslipidemia diagnosis. The long-term benefits of lipid screening and subsequent treatment in this population are uncertain.ObjectiveTo review benefits and harms of screening and treatment of pediatric dyslipidemia due to familial hypercholesterolemia (FH) and multifactorial dyslipidemia.Data SourcesMEDLINE and the Cochrane Central Register of Controlled Trials through May 16, 2022; literature surveillance through March 24, 2023.Study Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…31,32 The USPSTF evidence reviews from 2016 and 2023 summarized randomized clinical trial data and found no direct evidence of either effectiveness or harms of universal lipid screening in youths. 17,18 In contrast to AAP recommendations endorsing universal lipid screening, the USPSTF conclusion likely added confusion for clinicians regarding the necessity of cholesterol screening, which may negatively impact screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…31,32 The USPSTF evidence reviews from 2016 and 2023 summarized randomized clinical trial data and found no direct evidence of either effectiveness or harms of universal lipid screening in youths. 17,18 In contrast to AAP recommendations endorsing universal lipid screening, the USPSTF conclusion likely added confusion for clinicians regarding the necessity of cholesterol screening, which may negatively impact screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although universal lipid screening recommendations have been endorsed by the AAP since 2011, our findings may indicate that (1) health care professionals may not have a clear understanding of the childhood screening guidelines or (2) there may be barriers to changing screening and prevention practices . The USPSTF evidence reviews from 2016 and 2023 summarized randomized clinical trial data and found no direct evidence of either effectiveness or harms of universal lipid screening in youths . In contrast to AAP recommendations endorsing universal lipid screening, the USPSTF conclusion likely added confusion for clinicians regarding the necessity of cholesterol screening, which may negatively impact screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations